2018
DOI: 10.5505/tjtes.2018.68338
|View full text |Cite
|
Sign up to set email alerts
|

In the firearm injuries cases, the effect of correlation between injury severity score (ISS), vital scores, and hemogram values over mortality.

Abstract: BACKGROUND: Several scoring systems have been and continue to be developed in numerous countries with the goal of quickly and accurately assessing the severity of trauma injuries. The aim of this study was to identify factors that help to determine the gravity of damage and to minimize it, in order to reduce mortality and morbidity. It is important that the criteria set for the determination of the severity of trauma are objective, measurable, and comparable. This study was an assessment of the contribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In the present study, 97.72% of the cases were male, and 79.54% were aged 18-30 years. The study by Turan et al [10] demonstrated that the ISS value (>20) after GSWs was a factor with an effect on mortality, but it was not an independent risk factor alone. In the present study, the mean ISS value was 24.38 (12-43) and was 41 in a single patient who died.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, 97.72% of the cases were male, and 79.54% were aged 18-30 years. The study by Turan et al [10] demonstrated that the ISS value (>20) after GSWs was a factor with an effect on mortality, but it was not an independent risk factor alone. In the present study, the mean ISS value was 24.38 (12-43) and was 41 in a single patient who died.…”
Section: Discussionmentioning
confidence: 98%
“…Our modeling of ISS and GCS also highlights a method of domain adaptation as an alternative method for developing predictive algorithms 21 24 . Domain adaptation is the task of developing machine learning algorithms that can be easily transferred from one domain to another.…”
Section: Discussionmentioning
confidence: 99%